It Is Not Enough to Assess Conflicts of Interest When We Bring the Commercial Sector to the Policy Table; Comment on "Towards Preventing and Managing Conflict of Interest in Nutrition Policy? An Analysis of Submissions to a Consultation on a Draft WHO Tool" - Elisa Chilet-Rosell; Ildefonso Hernandez-Aguado (Kerman University of Medical Sciences, 2022)
Ralston et al offer us an interesting analysis of the consultation process of World Health Organization's (WHO's) "Draft approach on the prevention and management of conflicts of interests in the policy development and implementation of nutrition programs at country level," in which it shows us how the industry tries to frame the discussion in individual conflicts of interest, avoiding structural conflicts of interest. We must not forget other issues of importance in policymaking, such as the imbalance of power between different actors and the strategies of undue influence used by food and beverage corporations. It is essential to develop regulatory-based tools and procedures that embody ethics and good governance and that can be applied systematically and routinely to prevent corporate influence in health policymaking. A global observatory of corporate practices would also be needed to recommend to governments efficient actions to avoid corporate capture of their policies.